RELATIONSHIP BETWEEN HEMOGLOBIN LEVELS, BREAST MILK PRODUCTION, BLOOD TYPE, AND PSYCHOLOGICAL FACTORS WITH THE INCIDENCE OF BREAST MILK ENGORGEMENT IN POSTPARTUM MOTHERS - Kholifatul Ummah; Ainun Ganisya; Cityta Putri Kwarta (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Breast engorgement is a frequent postpartum complication that can interfere with breastfeeding and maternal comfort. This study aimed to examine the association between hemoglobin levels, breast milk production, psychological factors (measured by the Edinburgh Postnatal Depression Scale/EPDS), and blood group with breast engorgement among postpartum mothers. An analytic observational design with a cross-sectional approach was conducted on 100 postpartum mothers within the first seven days after delivery. Data were collected through clinical examinations, questionnaires, and laboratory tests. Bivariate analysis using the Chi-square test and multivariate logistic regression was applied with a significance level of p < 0.05. Results showed significant associations between breast milk production (p = 0.004) and EPDS scores (p = 0.021) with breast engorgement. Conversely, hemoglobin levels (p = 0.118) and blood group (p = 0.378) were not statistically significant predictors. Mothers with inadequate milk flow and higher EPDS scores were more likely to develop engorgement. The study concludes that breast engorgement is a multifactorial condition influenced by both physiological and psychological elements. This highlights the necessity of integrated postpartum care that includes mental health assessment, anemia screening, and breastfeeding education to improve lactation success.